2018
DOI: 10.3390/vetsci5010023
|View full text |Cite
|
Sign up to set email alerts
|

Avian Respiratory Coinfection and Impact on Avian Influenza Pathogenicity in Domestic Poultry: Field and Experimental Findings

Abstract: The avian respiratory system hosts a wide range of commensal and potential pathogenic bacteria and/or viruses that interact with each other. Such interactions could be either synergistic or antagonistic, which subsequently determines the severity of the disease complex. The intensive rearing methods of poultry are responsible for the marked increase in avian respiratory diseases worldwide. The interaction between avian influenza with other pathogens can guarantee the continuous existence of other avian pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 79 publications
1
51
1
Order By: Relevance
“…IBV causes upper respiratory illness, nephritic syndrome, and a drop in egg production in layer chickens [1]. The mortality rate can be high in young chickens, especially with other secondary complications such as viral and bacterial infections [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…IBV causes upper respiratory illness, nephritic syndrome, and a drop in egg production in layer chickens [1]. The mortality rate can be high in young chickens, especially with other secondary complications such as viral and bacterial infections [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between pathogens that have the same site of replication might be either synergistic or antagonistic determining the severity of the resulting clinical outcomes. The patterns of interaction can be influenced by the virulence of the strain, time of infection (pre-infection, simultaneously, or superinfection) bird immune response, biological products or metabolites, and/or other environmental risk factors [55,56].…”
Section: Viral Interactionmentioning
confidence: 99%
“…Despite their classification as LPAIV, they are associated with severe disease in poultry leading to significant economic losses [15,16]. It has been suggested that the strikingly distinct clinical signs induced in experimental and natural H9N2 infections are due to opportunistic viral and bacterial co-infections with H9N2 acting in synergy as an immunosuppressive agent [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%